Tinjauan Ekonomi Islam Terhadap Kredit Syariah - Fadli Hariadi; Dudi Badruzaman; Iwan Setiawan; Setya Indrawanto (AL-INTIFA, 2023)
This research was conducted based on the large number of financial institutions that provide working capital loans quickly through existing applications, which raises concerns that they will be trapped by usury practices. Meanwhile, research on Islamic credit can answer these concerns. This research uses qualitative methods, by collecting data then sorted and selected so that it becomes data that is easy to analyze and easy to form synthesis. The results of this study state that Sharia credit consists of two financings, namely Sharia working capital financing and Sharia investment financing, the financing is seen from the credit allocation, whether financing for murabahah, mudharabah, ijarah, istishna', salam, or IMBT (ijarah muntahia bit tamlik) loans. Sharia working capital financing short-term financing provided to companies or individuals to finance the working capital needs of their businesses based on Sharia principles, Working capital financing cannot be in the form of money but in the form of merchandise for resale by customers who apply for Sharia working capital financing, while the tenor given for Sharia working capital financing is a maximum of one year. Meanwhile, Sharia investment financing is medium-term or long-term financing for the purchase of necessary capital goods, including: (1) Establishment of new projects, namely the establishment or construction of projects / factories in the framework of new businesses. (2) Rehabilitation, i.e. the replacement of old damaged machinery/equipment with new, better machinery/equipment. (3) Modernization, namely the complete replacement of old machines / equipment with new machines / equipment with a better level of technology. . (4) Expansion, namely the addition of existing machinery/equipment with new machines/equipment with the same or better technology, or the relocation of an existing project, namely the transfer of the overall project/factory site (including supporting facilities for factory activities, such as laboratories and warehouses) from one place to another place with a better and strategic location. The tenor given for Sharia investment financing is a maximum of twelve years. Keywords: Sharia Credit, Sharia Working Capital, Sharia Investment.